Design of Crop Leaf Area Measurement using Webcam and Raspberry Pi - Hidayat; Muhammad Mahardiansyah (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2022)
This paper describes an electronic system for measuring the number of leaves and the total leaf area. This system is built to make it easier for users to compute several leaves and measure leaf area electronically. The number of leaves and leaf area are used to determine the level of fertility of a plant. Several important factors in measuring leaf area are the accuracy and the speed of measurement. The stages conducted in this research consist of needs analysis, design, implementation and testing. The system built uses a mini PC Raspberry Pi as the data processor and a webcam to capture images. Moreover, the image is processed using Binary threshold and Otsu threshold methods. The results showed that the designed system was functioning properly with an error rate of 0% for the number of leaves calculation and a 0.39% error rate in the of leaf area measurement.